NATURE OF NON-METALLIC IMPURITIES IN ECONOMICALLY-ALLOYED AUSTENITIC MANGANESE STEEL - A. I. Garost (Литьë и металлургия)
The characteristics of chrome-containing economically-alloyed steels are investigated. Micro-composition and nature of non-metallic impurities of steels with lowered content of manganese are studied. The optimal compositions of alloys for castings are offered.